Curing Lives Surviving the HIV Epidemic in Ethiopia - Nishi, Makoto (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This is a book about life during the HIV epidemic in Ethiopia, and seeks to understand how and why the global effort to achieve universal HIV treatment has shifted away from its initial focus on the excessive human suffering precipitated by the epidemic. When antiretroviral drugs became available in Ethiopia, they emerged as powerful agents of change: not only did they cure individuals, they also helped people overcome their fear of - and break the silence around - AIDS, while healing the social ruptures caused by the epidemic. Nevertheless, as this book argues, the very same agents have silently "reversed" these changes over the course of the past decade. These reversals have dissolved connections, re-incurred invisible social fissures, and allowed a large majority of people to stay indifferent to the suffering of individuals whose lives remain vulnerable under the current treatment regime. This whole process is a product of neoliberal global health interventions that determine which lives are worthy or unworthy of investment. This book will interest scholars of biopolitics and public health, those who study the developing world, and those interested in how pandemic interventions alter the lives of many. Makoto Nishi is an associate professor at the Graduate School of Humanities and Social Sciences, Hiroshima University. His current research projects focus on the care environment for families affected by some neurological conditions, including parasite-induced epilepsy in post-conflict northern Uganda and autism during Covid time in neoliberal Japan.
Chapter 1: Introduction -- Chapter 2: Initiating a new experimentation -- Chapter 3: Installation of a health system -- Chapter 4: In search of a cure -- Chapter 5: Life -- Chapter 6: Ajyet and jegna -- Chapter 7: Culture of defiance.
Keywords: Medicine and the humanities; Public health; Science -- History; Medical Humanities; Public Health; History of Science